Natural sesquiterpene lactones of the 4,15-iso-atriplicolide type are inhibitors of trypanothione reductase - Lenz, Mairin; Krauth-Siegel, Renate; Schmidt, Thomas J. (Molecules, 2019)
In the course of our investigations on the antitrypanosomal potential of sesquiterpene lactones (STL), we have recently reported on the exceptionally strong activity of 4,15-iso-Atriplicolide tiglate, which demonstrated an IC50 value of 15 nM against Trypanosoma brucei rhodesiense, the etiologic agent responsible for East African human trypanosomiasis (HAT). Since STLs are known to often interact with their biological targets (e.g., in anti-inflammatory and anti-tumor activity) by means of the covalent modification of biological nucleophiles—most prominently free cysteine thiol groups in proteins—it was a straightforward assumption that such compounds might interfere with the trypanothione-associated detoxification system of trypanosomes. This system heavily relies on thiol groups in the form of the dithiol trypanothione (T(SH)2) and in the active centers of enzymes involved in trypanothione metabolism and homeostasis. Indeed, we found in the present study that 4,15-iso-atriplicolide tiglate, as well as its structural homologues, the corresponding methacrylate and isobutyrate, are inhibitors of trypanothione reductase (TR), the enzyme serving the parasites to keep T(SH)2 in the dithiol state. The TR inhibitory activity was demonstrated to be time-dependent and irreversible. Quite interestingly, of the several further STLs with different core structures that were also tested, none inhibited TR at a significant level. Thus, the TR inhibitory effect by the 4,15-iso-atriplicolide esters appears to be specific for this particular type of furanoheliangolide-type STL. Some structure–activity relationships can already be deduced on the basis of the data reported here, which may serve as the starting point for searching further, possibly more potent, TR inhibitors.